The proposal of implementing a business model entailing the digitalization of the ARM system of Incepta Pharmaceuticals Limited - Islam, Saiyan (BRAC University, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2016.